Trauma KDRT dan Perilaku Posesif Remaja: Studi Kasus di Pusat Rehabilitasi Serang: Penelitian - Wiwin Sulistiyawati; Nadirah, Yahdinil Firda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This qualitative case study aims to explore the impact of witnessing Domestic Violence (DV) and parental divorce on adolescent mental health, focusing on the case of F (30 years old), who was treated at the "Welas Asih Indonesia Waras Ministry" Rehabilitation Center for Mentally Ill Persons (ODGJ) in Serang, Banten due to extreme possessive behavior towards her mother. This behavior is assumed to be deeply rooted in psychological trauma resulting from witnessing physical and psychological violence perpetrated by her father towards her mother since childhood. Using qualitative methods (in-depth interviews and observations), the results of the study indicate that the trauma of DV manifests as extreme possessive behavior in adolescence, characterized by constant clinging, monopolizing the mother's attention, and tantrums when attention is divided, which is consistent with characteristics of anxious-ambivalent attachment. The holistic intervention at the center, including individual counseling, daily activity therapy, and family counseling, has shown significant positive developments; Febra is now calmer, has fewer tantrums, and has improved emotional control, although she still faces challenges such as sometimes having incoherent speech and hallucinations.